Disputes of Investment Company Liquidation in the Libyan Commercial Law - Ali Matuq Ali Saleh (Journal of Libyan Academy Bani Walid, 2025)
This study examines liquidation disputes in investment companies under Libyan commercial law by analyzing relevant legal texts, primarily the Commercial Activity Law No. 23 of 2010, the Investment Promotion Law No. 9 of 2010, and the Capital Market Law No. 11 of 2010. The study aims to clarify the legal framework governing the liquidation process, the types of disputes that arise during it, and the legal procedures for resolving them, in addition to defining the liquidator’s role, powers, and legal responsibilities towards partners and creditors. The findings revealed that the Libyan legislator has established a comprehensive legal system for regulating the liquidation process; however, practical implementation faces challenges related to lengthy litigation procedures, weak alternative dispute resolution mechanisms, lack of specialized expertise in the field of liquidation, and absence of effective oversight of liquidators’ work. The study recommends developing commercial arbitration mechanisms, simplifying liquidation procedures, and strengthening judicial oversight of liquidators, along with the necessity of activating the role of the Capital Market Authority in supervising the liquidation of listed investment companies, and establishing a national registry of certified liquidators to ensure competence and transparency.